Profil temperamen dan kompatibilitas sosial pada kera ekor panjang betina (Macaca fascicularis) yang dipelihara di penangkaran - Helyana Yunistiray Putriliani; Henny Endah Anggraeni; Amelia Diyan Safitri; Adinda Darayani Azhar; Suryo Saputro (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2026)
Long-tailed macaques (Macaca fascicularis) may exhibit agonistic behavior when housed in groups due to individual incompatibility, which can negatively affect social stability and animal welfare in captive settings. Temperament assessment has been proposed as a useful approach for evaluating individual compatibility prior to grouping. This study aimed to identify the temperament profiles of individual female long-tailed macaques housed at the Primate Research Center, IPB University. Temperament assessment was conducted on 11 adult females divided into two cage groups using the human intruder test in the profile phase. Behavioral responses were categorized into five temperament types. The results showed that four individuals exhibited neutral–aggressive temperament, three neutral–affiliative, two neutral–anxious, one neutral–fearful, and one fearful–neutral temperament. Comparative analysis indicated that cage group B displayed a higher proportion of affiliative-oriented individuals and greater overall compatibility than cage group A.